PENGARUH E-TRUST, E-SERVICE QUALITY, DAN E-SATISFACTION TERHADAP LOYALITAS PELANGGAN PADA SHOPEE: STUDI KASUS PADA PENGGUNA SHOPEE DI PONOROGO - Dewi Nurkhomaria; Siti Chamidah; Dwi Warni Wahyuningsih (Gapenas Publisher, 2022)
This study aims to determine the effect of E-Trust, E-Service Quality, and E-Satisfaction on User Loyalty at Shopee. (Case Study on Shopee Customers in Ponorogo). The sample in this study was 100 people who met the criteria determined by the researcher. The sampling technique in this study used purposive sampling and the data collection technique used was by distributing questionnaires. The testing phase used includes instrument testing, coefficient of determination test and hypothesis testing. The analysis used in this research is multiple linear regression analysis. The results of this study indicate that: (1) E-Trust partially has no significant effect on Customer Loyalty, (2) E-Service Quality partially has no significant effect on Customer Loyalty, (3) E-Satisfaction partially has a significant effect on Customer Loyalty